การบริหารจัดการตามมาตรฐานการเรียนร่วม ของโรงเรียนแกนนำจัดการเรียนร่วม จังหวัดนครปฐม - กิติวัฒณ์กนกโชติ, ธัญญ์นลิน (วารสาร ศึกษาศาสตร์ มมร, 2016)
การวิจัยครั้งนี้ มีวัตถุประสงค์ 1) เพื่อศึกษาการบริหารจัดการตามมาตรฐานการเรียนร่วมของโรงเรียนแกนนำจัดการเรียนร่วม สำนักงานเขตพื้นที่การศึกษาจังหวัดนครปฐม 2) เพื่อศึกษาระดับการบริหารจัดการตามมาตรฐานการเรียนร่วมของโรงเรียนแกนนำจัดการเรียนร่วม จังหวัดนครปฐม ประชากรที่ใช้ในการวิจัย โรงเรียนแกนนำจัดการเรียนร่วม จังหวัดนครปฐม จำนวน 50 โรงเรียนเป็นหน่วยวิเคราะห์ ผู้ให้ข้อมูล ผู้บริหารสถานศึกษา โรงเรียนละ 1 คนรวม 50 คน เครื่องมือที่ใช้แบบสัมภาษณ์และแบบสอบถาม การวิเคราะห์ข้อมูล ใช้การวิเคราะห์เนื้อหา ค่าความถี่ ค่าร้อยละ ค่าเฉลี่ย ค่าส่วนเบี่ยงเบนมาตรฐาน ผลการวิจัย 1. ด้านคุณภาพผู้เรียน พบว่า เด็กได้รับการพัฒนาตามศักยภาพมีความรู้ความสามารถและทักษะตรงตามจุดประสงค์ที่กำหนดไว้ในแผนการจัดการศึกษาเฉพาะบุคคล มีระดับคุณภาพผู้เรียนในภาพรวมอยู่ในระดับมาก 2. ด้านการจัดการเรียนการสอน พบว่า ครูมีความรักความเมตตาเข้าใจความแตกต่าง ของเด็กมีเจตคติที่ดีต่อการจัดการเรียนร่วมและปฏิบัติต่อผู้เรียนอย่างเหมาะสม มีการฝึกอบรม เพื่อพัฒนาให้มีทักษะในการจัดการเรียนร่วมอยู่เสมอทั้งในหน่วยต้นสังกัดและนอกหน่วย ครูมีการจัดทำแผน IEP เป็นไปอย่างมีประสิทธิภาพและเกิดประสิทธิผลเป็นไปตามที่กระทรวงกำหนด แต่ยังขาดวิทยากรจากสถาบันต่าง ๆ มาให้ความรู้เรื่องของการทาสื่อและนวัตกรรมใหม่ ๆ และระดับการบริหารจัดการตามมาตรฐานการเรียนร่วมของโรงเรียนแกนนำจัดการเรียนร่วม มีระดับการจัดการเรียนการสอนในภาพรวมอยู่ในระดับมาก 3. ด้านการบริหารจัดการ พบว่า ผู้บริหารมีเจตคติที่ดีและมีวิสัยทัศน์ในการบริหารจัดการเรียนร่วม ให้ความเสมอภาคและเปิดโอกาสให้เด็กเข้ามาเรียนในระบบทำให้เด็กได้มีโอกาสพัฒนาเท่าเทียมกับเด็กปกติ มีการบริหารวางแผนและกำหนดเป้าหมายไว้ในแผนปฏิบัติการโรงเรียน แต่การประชาสัมพันธ์ทางเว็บไซต์และการติดป้ายโรงเรียนแกนนำจัดการเรียนร่วมยังมีการปฏิบัติน้อย และระดับการบริหารจัดการตามมาตรฐานการเรียนร่วมของโรงเรียนแกนนำจัดการเรียนร่วม มีระดับการบริหารจัดการในภาพรวมอยู่ในระดับมาก 4. ด้านการสร้างสังคมแห่งการเรียนรู้ พบว่า ผู้บริหารส่งเสริมสนับสนุนการแลกเปลี่ยนเรียนรู้ด้านการจัดการเรียนร่วมระหว่างบุคลากรภายในสถานศึกษา พัฒนาแหล่งเรียนรู้ภายในและภายนอกจัดให้เหมือนกับเด็กปกติทั่วไปใช้การประเมินผลในภาพรวม ส่วนการติดตามประเมินผลดูจากรายงานโครงการที่วางไว้ในแผนปฏิบัติงานยังมีการปฏิบัติได้น้อย และระดับการบริหารจัดการตามมาตรฐานการเรียนร่วมของโรงเรียนแกนนำจัดการเรียนร่วม มีระดับการสร้างสังคมแห่งการเรียนรู้ในภาพรวมอยู่ในระดับมาก 5. ด้านผลกระทบจากการดำเนินงาน พบว่า ไม่มีผลกระทบที่รุนแรงครูรู้จักการเอื้อเฟื้อเผื่อแผ่และช่วยเหลือเด็กพิเศษ ชุมชนผู้ปกครองที่เข้าใจเด็กที่มีความต้องการพิเศษให้การชื่นชมและให้การสนับสนุนกิจกรรมของโรงเรียนและรู้สึกดีที่โรงเรียนให้ความสำคัญกับเด็กพิเศษ ส่วนผู้ปกครองที่ยังไม่เข้าใจคำว่าเด็กที่มีความต้องการพิเศษคิดว่าเป็นเด็กพิการอย่างเดียวจึงไม่ให้ความร่วมมือ และระดับการบริหารจัดการตามมาตรฐานการเรียนร่วมของโรงเรียนแกนนำจัดการเรียนร่วม มีระดับผลกระทบจากการดำเนินงานในภาพรวมอยู่ในระดับมาก 6. ด้านประโยชน์จากการดำเนินงาน พบว่า โรงเรียนได้รับชื่อเสียงในด้านดี ผู้ปกครองมีความรู้สึกที่ดีต่อโรงเรียนเนื่องจากเด็กได้รับการพัฒนาฯ ทำให้ช่วยเหลือตนเองและทาประโยชน์ให้กับสังคมได้ และระดับการบริหารจัดการตามมาตรฐานการเรียนร่วมของโรงเรียนแกนนำจัดการเรียนร่วม มีระดับประโยชน์จากการดำเนินงานในภาพรวมอยู่ในระดับมาก 7. ด้านความคิดเห็นอื่น ๆ ในการการบริหารจัดการ พบว่า เด็กที่มีความต้องการพิเศษ มีจำนวนเพิ่มมากขึ้นเรื่อย ๆ ในการจัดการเรียนร่วมมีงบประมาณไม่เพียงพอในการบริหาร จึงต้องการให้หน่วยงานในท้องถิ่นเข้ามาสนับสนุน รัฐบาลควรมีนโยบายหรือระบบเข้ามาช่วยเหลือดูแลมากขึ้นรวมถึงโรงเรียนยังขาดบุคลากรที่มีความรู้ด้านการศึกษาพิเศษโดยตรงมาช่วยดูแล และระดับการบริหารจัดการตามมาตรฐานการเรียนร่วมของโรงเรียนแกนนำจัดการเรียนร่วม มีระดับความคิดเห็นอื่น ๆ เกี่ยวกับการบริหารจัดการในภาพรวมอยู่ในระดับมาก ABSTRACT The purposes of this research were 1) to study the management based onthe inclusive education standards of leading inclusive schools in Nakhon Pathom Province, and 2) to study the situation of the management of the leading inclusive schools as earlier mentioned. The population consisted of 50 administrators of 50 primary schools situated in Nakhon Pathom Province. The tools used for data collection were interview and constructed questionnaire. The statistic devices used for data analysis comprised frequency, percentage, mean and standard deviation. The results of study were as follows: 1. Quality of learners: It was found that the pupils’ potential in terms of both intelligence and skills had been developed to meet with the objectives as defined in the individualized education plan. The measurement and evaluation in the short and long term was found to work ineffectively, the semester-based method was therefore used instead. On an overall aspect, the learners’ quality was found to stand at a high level. 2. Teaching management: The teachers were found to have a sense of loving-kindness and realize the concept of individual difference, and they also adopted a good attitude towards the inclusive education and treated the pupils in an appropriate manner. Moreover, the training program about the inclusive education was organized regularly both inside and outside, and an IEP lesson plan was worked out to meet with the ministry requirements. But what was found in need was the out-resource to teach and train how to invent instructional media and innovation. On an overall aspect, the teaching management was found to exist at a high level.   3. Situation of management: The administrators were found to have a good attitude and vision about the inclusive education management. The special children were provided with a wider opportunity to study in the inclusive school, and their intelligence and skills were developed as equally as the ordinary children. The school’s action plan and goal setting were designed, but few public information in a website and the school boards were found. On an overall aspect, the management based on the inclusive education standards was found to remain at a high level. 4. Building knowledge-based society : The exchanging of views about the inclusive education among the teachers inside and outside was promoted by the administrators. The development of learning resources for special children was implemented as similarly as those arranged for ordinary children. The assessment of their performances was carried out on an overall basis. However, very few progress was found in the assessment of the school’s action plan. On an overall aspect, the building of knowledge-based society was found to remain at a high level. 5. Impacts caused by management: Positive impacts were found as the teachers fostered a sense of hospitality and took a proper care for the special children. The guardians and the community members appreciated and supported the school’s activities, despite somewhat non-cooperation expressed by a fraction of those without right understanding. On an overall aspect, the positive impacts caused by the management of inclusive education were found to remain at a high level. 6. Benefits of management :The school was found to win public recognition and fame. The guardians’ attitude towards the school was positive in view of their children’s great development to the extent that they could help themselves and render social service to community. On an overall aspect, the benefits generated by the management of inclusive education were found to remain at a high level. 7. Recommendations : The number of special children was found to be ever-increasing, thus causing an insufficient budget allocation which needs financial support from local administrations as well as more budgeting by the government. Another important problem was the lack of teachers who graduated with major in the field of special education. On an overall aspect, the recommendations for the management of inclusive education to meet with the inclusive education standards as set by the Ministry of Education were found to remain at a high level.